Loss of Notch3 Signaling in Vascular Smooth Muscle Cells Promotes Severe Heart Failure Upon Hypertension. Issue 2 (August 2016) - Ragot, Hélène; Monfort, Astrid; Baudet, Mathilde; Azibani, Fériel; Fazal, Loubina; Merval, Régine; Polidano, Evelyne; Cohen-Solal, Alain; Delcayre, Claude; Vodovar, Nicolas; Chatziantoniou, Christos; Samuel, Jane-Lise
Abstract : Hypertension, which is a risk factor of heart failure, provokes adaptive changes at the vasculature and cardiac levels. Notch3 signaling plays an important role in resistance arteries by controlling the maturation of vascular smooth muscle cells. Notch3 deletion is protective in pulmonary hypertension while deleterious in arterial hypertension. Although this latter phenotype was attributed to renal and cardiac alterations, the underlying mechanisms remained unknown. To investigate the role of Notch3 signaling in the cardiac adaptation to hypertension, we used mice with either constitutive Notch3 or smooth muscle cell–specific conditional RBPJκ knockout. At baseline, both genotypes exhibited a cardiac arteriolar rarefaction associated with oxidative stress. In response to angiotensin II–induced hypertension, the heart of Notch3 knockout and SM- RBPJκ knockout mice did not adapt to pressure overload and developed heart failure, which could lead to an early and fatal acute decompensation of heart failure. This cardiac maladaptation was characterized by an absence of media hypertrophy of the media arteries, the transition of smooth muscle cells toward a synthetic phenotype, and an alteration of angiogenic pathways. A subset of mice exhibited an early fatal acute decompensated heart failure, in which the same alterations were observed, although in a more rapid timeframe. Altogether, these observations indicate that Notch3 plays a major role in coronary adaptation to pressure overload. These data also show that the hypertrophy of coronary arterial media on pressure overload is mandatory to initially maintain a normal cardiac function and is regulated by the Notch3/RBPJκ pathway. Abstract : Supplemental Digital Content is available in the text.